Dimensi Struktur Modal pada Perusahaan Property and Real Estate - Fida Nur Annisa; Yuli Chomsatu Samrotun; Rosa Nikmatul Fajri (Politeknik Ganesha Medan, 2020)
Capital structure is a balance or comparison between foreign capital and own capital. This study aimsto examine and analyze the effect ofprofitability, non-debt tax shield, asset structure, company size, and liquidity in property and real estate companies in 2015-2018. The independent variables of this study are profitability, non-debt tax shield, asset structure, company size, and liquidity. The dependent variable in this study is the capital structure. This study uses secondary data obtained from the IDX. With a population of 48 property and real estate manufacturing companies and sampling techniques using purposive sampling produces 34 sample companies. This type of quantitative research and data analysis techniques using multiple linear regression. The results of the research partially addressed the variable profitability, company size and liquidity which had no significant effect on capital structure while the non-debt tax shield and asset structure variables had a significant effect on capital structure.